RESEARCH OF FAST-ACTION OF THE DIRECT DIGITAL METHOD OF SPECTRAL CORRELATIVE-INTERFEROMETRIC DIRECTION FINDING WITH DOUBLE CORRELATION PROCESSING - Tsyporenko, V. V.; Tsyporenko, V. G.; Khomenko, M. F. (Radio Electronics, Computer Science, Control, 2017)
Contex. At present, the direction finding of radio electronic means should be carried out under conditions of a complex electromagnetic situation, a large a priori uncertainty regarding the parameters of radio emissions, and also in conditions of a real-time implementation. A promising direction in the direction finding implementation for these conditions is the use of broadband digital correlation-interferometric radio direction finders. Objective. The aim of the article is to estimate the total time costs, speed and relative time efficiency of the direct digital method of spectral correlative-interferometric direction finding with double correlation processing. Method. Analytic studies of total time costs of correlation-interferometric direction finding algorithms and experimental studies of relative time efficiency are performed in the work. Results. Analytical estimation of total time costs, speed and relative time efficiency of the direct digital method of spectral correlativeinterferometric direction finding with double correlation processing is performed. With minimal hardware costs, that is, using a single-channel data processing system, it is determined that the investigated direct direction finding method provides direction finding of radio emissions entering the frequency band of simultaneous analysis with a possible width of up to 500 MHz in real time. The investigated direction finding method has relative time efficiency in 100 times higher in comparison with the known search digital spectral correlation-interferometric method of direction finding. Conclusions. Comparative analysis has shown that the investigated direction finding method has a high relative time efficiency exceeding 100 times in comparison with the known search digital spectral correlation-interferometric method of direction finding.